DYNAMICS OF CLINICAL AND LABORATORY INDICATORS IN THE TREATMENT OF PATIENTS WITH PSORIASIS AND CONCOMITANT ALIMENTARY OBESITY - Yemchenko, Ya.A.; Ishcheikin, K.Ye.; Kaidashev, I.P. (World of Medicine and Biology, 2020)
Psoriasis is the most common chronic, genetically determined autoimmune polyetiological inflammatory disease with impaired epidermal proliferation, which is provoked by exogenous and endogenous factors and is manifested by erythematous and scaly elements, papules and plaques. There is still no consensus on the pathogenesis of this dermatosis. To objectively understand the pathogenesis of psoriasis, it is necessary to take into account the insufficiently studied comorbidity of this pathology. Numerous studies have shown a clear link between psoriasis and obesity. Systemic inflammation is a common link in the pathogenesis of obesity and psoriasis. In this study, we determined the effectiveness of standard treatment for patients with psoriasis and concomitant grade I-II alimentary obesity, by clinical and immunological examination of systemic inflammation. Found that the treatment of patients was ineffective and further led to the deterioration of patient’s condition due to increased systemic inflammation, the progression of obesity and a more severe course of psoriasis.